Obesity does not lead to imbalance between myocardial phospholamban phosphorylation and dephosphorylation - Freire, Paula Paccielli [UNESP]; Alves, Carlos Augusto Barnabe [UNESP]; de Deus, Adriana Fernandes [UNESP]; Leopoldo, Ana Paula Lima; Leopoldo, André Soares; da Silva, Danielle Cristina Tomaz [UNESP]; de Tomasi, Loreta Casquel [UNESP]; Campos, Dijon Henrique Salomé [UNESP]; Cicogna, Antonio Carlos [UNESP] (Sociedade Brasileira de Cardiologia, 2014)
Background: The activation of the beta-adrenergic system promotes G protein stimulation that, via cyclic adenosine monophosphate (cAMP), alters the structure of protein kinase A (PKA) and leads to phospholamban (PLB) phosphorylation. This protein participates in the system that controls intracellular calcium in muscle cells, and it is the primary regulator of sarcoplasmic reticulum calcium pump activity. In obesity, the beta-adrenergic system is activated by the influence of increased leptin, therefore, resulting in higher myocardial phospholamban phosphorylation via cAMP-PKA. Objective: To investigate the involvement of proteins which regulate the degree of PLB phosphorylation due to beta-adrenergic activation in obesity. In the present study, we hypothesized that there is an imbalance between phospholamban phosphorylation and dephosphorylation, with prevalence of protein phosphorylation. Methods: Male Wistar rats were randomly distributed into two groups: control (n = 14), fed with normocaloric diet; and obese (n = 13), fed with a cycle of four unsaturated high-fat diets. Obesity was determined by the adiposity index, and protein expressions of phosphatase 1 (PP-1), PKA, PLB, phosphorylated phospholamban at serine16 (PPLB-Ser16) were assessed by Western blot. Results: Obesity caused glucose intolerance, hyperinsulinemia, hypertriglyceridemia, hyperleptinemia and did not alter the protein expression of PKA, PP-1, PLB, PPLB-Ser16. Conclusion: Obesity does not promote an imbalance between myocardial PLB phosphorylation and dephosphorylation via beta-adrenergic system.
Keywords: Adyposity; Leptin; Obesity; Phosphorylation; Rats